Integrative taxonomic description of Plakina kanaky, a new polychromatic sponge species from New Caledonia (Porifera: Homoscleromorpha). (27th September 2014) - Ruiz, César; Ivanišević, Julijana; Chevaldonné, Pierre; Ereskovsky, Alexander V.; Boury‐Esnault, Nicole; Vacelet, Jean; Thomas, Olivier P.; Pérez, Thierry
Abstract: Four similar sponges of different colors, all unknown to science, were collected in submarine caves of New Caledonia. We aimed at determining whether the four chromotypes represented different species or phenotypic variations of a unique new species. We used an integrative taxonomic approach combining morphologic, molecular and metabolomic analyses. The main traits that define these specimens are a skeleton made of monolophose, trilophose and tetralophose calthrops only, high chemical diversity and a high abundance and diversity of prokaryotic symbionts. The symbiotic community includes two unique prokaryote morphotypes, which are described for the first time in Homoscleromorpha, and appeared to be vertically transmitted. Although several features slightly differ among chromotypes, the most parsimonious conclusion was to propose a single new species Plakina kanaky sp. nov. Our phylogenetic analysis indicated the paraphyly of the Plakina genus, with P. kanaky sp. nov. belonging to a clade that includes Plakina jani and Plakina trilopha . The present work demonstrates that integrative taxonomy should be used in order to revise the entire Plakinidae family and especially the non‐monophyletic genus Plakina .